What MFTs should know about nutrition, psychosocial health, and collaborative care with nutrition professionals. (15th July 2021) - Novak, Josh R.; Robinson, Lindsey P.; Korn, Leslie E.
Abstract: Despite sufficient evidence on the role of nutrition in psychosocial health, Marriage and Family Therapists lack the knowledge for sufficient assessment and referrals in treatment. The purpose of this article is to orient MFTs to human metabolism and the effects of various nutrients, or lack thereof, on the psychosocial health in their clients. The roles of several micronutrients and macronutrients will be described as well as the effects of eating patterns and overall metabolic health on mental health. Finally, implications for MFTs as sole practitioners, domains for assessment and psychoeducation, and recommendations for collaborating with nutrition professionals will be discussed.